THE INFLUENCE OF DARUL AHDI WA SYAHADAH'S NATIONAL LEARNING ON THE UNDERSTANDING OF RELIGIOUS NATIONALIST ATTITUDES IN PRIMARY SCHOOL STUDENTS - Erika Wahyu Stefani; Muhlasin Amrullah; Khizanatul Hikmah (SOSIOEDUKASI, 2025)
Study aim For analyze impact from learning Darul Ahdi Wa nationality Shahadah to understanding attitude nationalist and religious student Grade IV of Cemengkalang State Elementary School. The method used is Pre Experimental Design with pre-test and post-test measurements were conducted on 28 students. The research This includes validity test, reliability test , N-Gain test, normality test, and paired test. Learning This combine values nationality and religiosity, with hope can increase understanding student about attitude nationalist and religious. The main goal education is For form moral character and improve intelligence. At the age of school basic, character student tend prone to to influence negative developing digital technology moment this. Through learning this, students pushed For in a way active participate in activities that reflect values The results of the research show that effective learning​ No only repair knowledge academic, but also form character student as a generation that loves homeland and​ uphold religious values. Research this is also expected can give contribution for development of more educational programs good, effective, and increase quality education that is oriented towards formation character strong nation​ at a time grow a sense of love to homeland and responsibility answer social.